Congenital Absence of Pericardium: A Rare Case Associated with Severe Mitral Stenosis with Pulmonary Hypertension - Zulkarnine, MI; Choudhury, BMM; Islam, MF; Ahmed, N (Cardiovascular Journal, 2011)
We report a rare case of congenital absence of pericardium in a 35 year old middle-aged man, who underwent closed mitral commissurotomy done for severe mitral restenosis developed after Percutaneous Transluminal Mitral Commissurotomy (PTMC) six months back. Operation was done under General Anaesthesia through left anterolateral thoracotomy. Pericardial defect was discovered intraoperatively. There was no clinical symptom that could be clearly related to the defect of the pericardial sac pre-operatively. The recovery of the patient was satisfactory and uneventful. Key Words: Mitral stenosis; Absent pericardium. DOI: http://dx.doi.org/10.3329/cardio.v3i2.9193 Cardiovasc. J. 2011; 3(2): 222-225